2020
DOI: 10.1148/ryct.2020200130
|View full text |Cite
|
Sign up to set email alerts
|

CT Features and Short-term Prognosis of COVID-19 Pneumonia: A Single-Center Study from Kashan, Iran

Abstract: Typical CT features of COVID-19 pneumonia include bilateral lung involvement in form of ground-glass opacities, predominantly in peripheral posterior distribution with lower lung zone predilection. • Subpleural sparing and pleural effusion are seen approximately in one-fifth and onesixth of our COVID-19 cases respectively. • Consolidation, air-bronchograms, central lung involvement and pleural effusion on initial CT chest have prognostic value, seen significantly more in ICU admitted and expired cases. Summary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
86
3
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 17 publications
10
86
3
4
Order By: Relevance
“…Yu et al reported that extension of the disease, pleural effusion, interlobular septal thickening and air bronchogram are more common in severe form of the disease [ 12 ]. Our prior published study also demonstrated that consolidation, air bronchogram, central lung involvement, pleural effusion and crazy paving are more common in ICU admitted and expired patients [ 10 ]. In this statistically stronger case-control study based on a multivariate regression analysis, none of these morphological and locational features were significant predictors of mortality in healthy nonelderly COVID-19 pneumonia patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al reported that extension of the disease, pleural effusion, interlobular septal thickening and air bronchogram are more common in severe form of the disease [ 12 ]. Our prior published study also demonstrated that consolidation, air bronchogram, central lung involvement, pleural effusion and crazy paving are more common in ICU admitted and expired patients [ 10 ]. In this statistically stronger case-control study based on a multivariate regression analysis, none of these morphological and locational features were significant predictors of mortality in healthy nonelderly COVID-19 pneumonia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying admitting CT predictors of mortality in nonelderly healthy patients without underlying medical conditions will aid to distinguish the most vulnerable patients in this age group and thus alter the management. A few more recently published observational studies have proposed potential imaging-based prognostic indices to predict mortality [ [10] , [11] , [12] ], but statistically higher-level studies are warranted. To our knowledge, a dedicated case-control study has not yet been performed for the assessment of radiological prognostic factors in COVID-19 pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Risk of bias with respect to patient spectrum was rated "unclear" in two studies, 34,39 because the number of patients with normal chest CT imaging findings was not reported. Risk of bias with respect to flow and timing was rated "unclear" in 24 studies, 15,16,[18][19][20][21][22][23][24][26][27][28][29][30][31][32][34][35][36][37][38][39][40][41] because these studies did not report the time interval between CT scanning and RT-PCR/gene sequencing. Risk of bias with respect to flow and timing was rated "high" in two studies, 14,25 because the time interval between CT and RT-PCR procedures exceeded 72 hours (maximum of 7 and 14 days, respectively).…”
Section: Methods Of Patient Selectionmentioning
confidence: 99%
“…Risk of bias with respect to observer variation was rated "high" in 27 studies, 40,41 because these studies did not report data on observer agreement. Finally, risk of bias in the domain blinding to the reference standard was rated "unclear" in 14 studies, 15,16,20,22,23,27,[30][31][32][34][35][36][37]41 because these studies did not report whether the interpreters of chest CT scans were blinded to the RT-PCR results.…”
Section: Methods Of Patient Selectionmentioning
confidence: 99%
“…CT is indicated in patients with functional respiratory impairment and/or hypoxemia after recovery from COVID-19 [ 6 ]. CT scan has been used not only for the initial assessment of the lung involvement and its extent but also to predict the prognosis and mortality, identify the complications, guide treatment plans, and monitor the pulmonary findings of the patients after treatment [ 7 10 ]. In order to reduce the radiation dose and cancer risk, chest CT can be performed by low-dose protocols in COVID-19 patients with high accuracy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%